Nationalism in Europe and America : Politics, Cultures, and Identities since 1775 - Kramer, Lloyd S. (Book collections on Project MUSE., 2011)
Nationalism in Europe and America analyzes the multiple historical contexts and intellectual themes that have shaped modern nationalist cultures, including the political claims for national sovereignty, the emergence of nationalist narratives in historical writing and literature, the fusion of nationalism and religion, and the overlapping conceptions of gender, families, race, and national identities. Kramer emphasizes the similarities in American and European nationalist thought, showing how European ideas about land, history, and national destiny flourished in the United States while America ...